Long-term care medicine a pocket guide - Fenstemacher, Pamela Ann; Winn, Peter (Current clinical practice., 2011)
Long-Term Care Medicine: A Pocket Guide lessens the uncertainty involved in caring for patients in a long-term care facility. This practical pocket guide is divided into four sections: Introduction, Common Clinical Conditions, Psychosocial Aspects, and Special Issues in Long-Term Care. The chapters address all the varied components of the LTC system as well as how to take care of the patients and residents living within it. The contributors to this easy-to-read guide are passionate about LTC and many have worked within the American Medical Directors Association to create and disseminate a knowledge base for practitioners. Long-Term Care Medicine: A Pocket Guide is an invaluable resource for clinicians, practitioners, and educators who are seeking to optimize the care and living experience of residents in LTC by providing resident-centered care as well as resident choice, well-being, dignity, and an improved quality of life.